(untitled) (Educational Dimension, 2025)
This study examines how personal reading preferences, abilities, and cultural influences shape the reading habits and well-being of postgraduate students in a Nigerian tertiary institution. Using a descriptive survey design, data was collected from 310 students through questionnaires. Findings reveal that personal preferences strongly influence reading format choices, with 50.3% of respondents agreeing and 24.9% strongly agreeing (mean = 3.85, SD = 0.99). In contrast, peer and societal pressures have a weaker influence (mean = 2.37 and 2.42, respectively). Students exhibit high proficiency in using both digital (mean = 3.86, SD = 0.90) and physical reading materials (mean = 3.91, SD = 0.88), but they face greater challenges with digital platforms (mean = 2.58, SD = 1.16) compared to physical materials (mean = 2.31, SD = 1.07). Environmental factors significantly impact reading choices (mean = 3.27, SD = 1.05), while cultural influences elicit mixed responses (mean = 2.86, SD = 1.11). Religion emerges as a strong motivator for reading habits (mean = 3.77, SD = 1.06). Regression analysis establishes a significant association between individual factors and reading habits and well-being (R = 0.465, p = 0.000). Key predictors include personal preference (β = 0.069, p = 0.001), physical reading due to upbringing (β = 0.070, p = 0.000), and belief in the benefits of digital platforms (β = 0.070, p = 0.001). Based on these insights, the study recommends that universities and libraries develop bibliotherapy programs that prioritize personal preferences and provide diverse reading materials. Acknowledging the limitation of self-reported data, future research could incorporate objective measures such as digital reading logs to enhance accuracy and depth.